Soluble Dietary Fiber from Aloe Vera and Lady’s Finger; Effect on Glucose Absorption in Type-2 Diabetic Model Rats - Afrin, F.; Hossain, M. S.; Amin, M. T.; Islam, M. M.; Rokeya, B. (Journal of Scientific Research, 2021)
Despite considerable progress in diabetes mellitus by conventional synthetic drugs, the search for natural anti-diabetic plant products is going on. The effects of soluble dietary fibre (SDF) of Aloe Vera and Lady’s Finger on glucose absorption were evaluated by the gut perfusion method in Type-2 diabetic model rats. SDFs were extracted from Aloe Vera and Lady’s Finger by enzymatic digestion method. Both the SDF extracts of Aloe Vera and Lady’s Finger and glucose (control) suspended in buffer solution at a dose of 1.25 g/kg were perfused at a rate of 0.5 mL/min for 30 min through the gut. The % of glucose absorption observed for up to 30 min. The % of glucose absorption for Aloe Vera and Lady’s Finger during the 30 min was 52.98±5.67 and 57.74±4.81, respectively, compared to control 67.74±8.62. The p-value (0.061) for Aloe Vera was quite closer to the level of significance. On the other hand, Lady’s Finger had a non-significant effect on glucose absorption (p=0.145) in Type-2 diabetic model rats' gut. The results suggested the therapeutic potential of the SDF of Aloe Vera and Lady’s finger, which suppressed postprandial hyperglycemia after glucose ingestion.